Perceptions of Image-Based Sexual Abuse Among the American Public - McCall, Corey (Criminology, criminal justice, law & society, 2021)
Image-based sexual abuse (IBSA) involves the sharing or distribution of erotic material without the consent of the subject in the material. A common scenario of IBSA revolves around an individual sharing erotic material of their former intimate partner following the dissolution of the relationship in order to humiliate or harass that former partner for a perceived wrongdoing. This scenario has caused IBSA to be referred to as "revenge porn" in the past, but that phrase does not capture the full breadth of IBSA behaviors and motivations. IBSA is a relatively new phenomenon, having emerged in the last decade, and few studies have examined public perceptions of the activity. In the present study, the attitudes of a national sample (_n_ = 1,023) of Americans were examined on IBSA-related issues. Results of this study showed that the general public largely disapproves of IBSA and supports its criminalization; however, the public also attributes blame to the victims of IBSA. Several factors influence these perceptions including sex, race, age, parental status, political orientation, and sexting history.